The Influence of Tourist Motivation on Tourist Visit Decision During Visit Keraton Cliffts Bandung - Gamma Bhakti Pradana; Puspo Dewi Dirgantari; Agus Rahayu (Dinasti International Journal of Management Science, 2023)
Tebing Keraton as a new and well-known tourist destination seeks to increase tourist visit decisions by increasing their tourist motivation. The main purpose of this study is to prove the influence of tourist motivation on visit decisions at Tebing Keraton. The data collection method was carried out using an online questionnaire. The sample of respondents obtained was 50 respondents with a purposive sampling technique. Data analysis using simple linear regression. This study shows that tourist motivation has a significant influence on visit decisions. it is felt that the components of the push and pull factors of tourists need to be maintained and improved in order to attract tourists to visit the Keraton Cliff.